Russia-Ukraine War’s Effects on Southeast Asian Countries’ Economics - Yuniarto, Bambang; Nisa, Leli Kudriyati; Junaedi, Tita Noviana Tiarni; Yanto, Handi; Shufiyyati, Shufiyyati (Indonesian Journal of Multidisciplinary Science, 2023)
The war between Russia and Ukraine has had important consequences for global markets. Russia is a country that has the activities of producers and exporters of oil, natural gas exporters of coal. while Ukraine is obliged to jointly implement the global market, namely exporters of oil, sunflower, corn, and wheat. These two countries are major suppliers in every deficit country such as those in Southeast Asia, active wars causing an increase in oil prices in the world that have an impact on the Southeast Asian region. The purpose of the study is to describe and analyze the existing economy in the Southeast Asian region due to the impact of the Russia-Ukraine war. This study utilizes qualitative methods in this type of descriptive analytical study, then the researcher not only lays out the impact of the war between Russia and Ukraine on the Southeast Asian economy but also to analyze the economic ties between Southeast Asian countries and Russia. Among ASEAN's main trade as well as only bilateral trade 0.66% of ASEAN's total trade turnover. Southeast Asia is feeling the direct impact of wars such as global supply chain disruptions and rising energy and food figures. Coupled with the increase in fuel prices of various countries, the problem made a big impression on the impact of the war between Russia and Ukraine in various aspects, leading to the restructuring of the global economy.